1.4 Interventional Pulmonology 2016
DOI: 10.1183/13993003.congress-2016.pa774
|View full text |Cite
|
Sign up to set email alerts
|

A single-center comparison of the cost analyses of different volume reduction-therapy methods in the treatment of emphysema

Abstract: ÖzPurpose: The aim of this study was to evaluate and compare preoperative and postoperative one year-cost analyses of endobronchial valve and enbronchial coil practices and volume-reduction surgical methods applied for the purpose of reducing volume in the patients with emphysema. Material and Methods: All the data regarding the oneyear-preoperative and postoperative hospital costs of the patients in our hospital, 11 of whom received an endobronchial valve, 9 of whom received an endobronchial coil and 7 of who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“… 37 Simon et al, in their study of the EBC in 2017, reported an increase in FEV1 from 0.5 L to 0.6 L (0.1 L) and a decrease in RV from 6.1 to 5.6.11 Metin et al, reported a 54.0% increase in FEV1 after the valve procedure, and 44% after the coil procedure. 38 In our study, among the patients who underwent EBV, we observed a 380 mL increase in FEV1 ( P <.001), and 270 mL decrease in RV ( P <.001). A signifi-cant improvement was found in each parameter after application.…”
Section: Discussionsupporting
confidence: 46%
“… 37 Simon et al, in their study of the EBC in 2017, reported an increase in FEV1 from 0.5 L to 0.6 L (0.1 L) and a decrease in RV from 6.1 to 5.6.11 Metin et al, reported a 54.0% increase in FEV1 after the valve procedure, and 44% after the coil procedure. 38 In our study, among the patients who underwent EBV, we observed a 380 mL increase in FEV1 ( P <.001), and 270 mL decrease in RV ( P <.001). A signifi-cant improvement was found in each parameter after application.…”
Section: Discussionsupporting
confidence: 46%